$\frac{2x-1}{5}$ -$\frac{x-2}{3}$ =$\frac{x+5}{6}$ +1

Question

$\frac{2x-1}{5}$ -$\frac{x-2}{3}$ =$\frac{x+5}{6}$ +1

in progress 0
Adalyn 2 tháng 2021-10-06T14:48:47+00:00 1 Answers 3 views 0

Answers ( )

    0
    2021-10-06T14:49:50+00:00

    Đáp án + Giải thích các bước giải:

    `(2x-1)/(5)-(x-2)/(3)=(x+5)/(6)+1` 

    `<=>(6(2x-1))/(30)-(10(x-2))/(30)=(5(x+5))/(30)+(30)/(30)`

    `<=>6(2x-1)-10(x-2)=5(x+5)+30`

    `<=>12x-6-10x+20=5x+25+30`

    `<=>12x-10x-5x=6-20+25+30`

    `<=>-3x=41`

    `<=>x=-(41)/(3)`

    Vậy `S={-(41)/(3)}`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )